Energy policy in Turkey’s development plans - Esen, Şaban; Akça, Yaşar; Özer, Gökhan; Akça, Yaşar; Esen, Şaban (Journal of Business & Economic Policy, 2017)
The five-year development plans which are prepared by Ministry of Development, State Planning Organization (SPO) formerly, are the basic policy documents revealing the growth that Turkey will realize in economic, social and cultural fields in the long term. A country's energy policy is primarily identified in development plans. The elements such as the availability of energy sources, sustainability of resources, methods of production, distribution and consumption efficiency are should be noted. The objectives of this study can be described as revealing the preparations for development plans to be prepared for future periods specifically ones in area of energy policy, attention toexisting and potential problems and making recommendations for the sector by offering solutions to the problems identified.
Keywords: Energy policy; Energy sources; Energy production; Energy consumption; Enerji politikası; Enerji kaynakları; Enerji üretimi; Enerji tüketimi